Sharia Arbitration and Business Dispute Resolution under Law No. 30 of 1999 - Hamidah, Al Milla; Isman; Hakim, Lukmanul (Journal of Islamic Economic Studies, 2025)
This study examines the consistency of legal norms governing Islamic arbitration institutions in Indonesia, focusing on the National Sharia Arbitration Board (BASYARNAS) within the framework of Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution. It aims to evaluate the extent to which BASYARNAS aligns with national legal principles and international standards in resolving business disputes. Using a normative juridical method and qualitative analysis of primary and secondary legal materials. The study identifies a significant gap between regulatory norms and practical implementation. This inconsistency undermines BASYARNAS’s effectiveness, particularly in resolving investment-related disputes from the perspective of foreign investors. The findings reveal weak integration of Islamic arbitration mechanisms into Indonesia’s broader legal system. Moreover, limited international recognition and misalignment with global procedural standards reduce investor confidence. The study concludes that regulatory harmonization, institutional reform, and enhanced global acknowledgment are necessary to strengthen BASYARNAS as a credible and competitive dispute resolution forum in the international investment arena.